A Chinese Branch Campus in Malaysia—Adjusting Fundamentals - Yingfei He, Bonnie; Ruby, Alan (International Higher Education, 2017)
The first overseas campus established by a renowned Chinese university- Xiamen University Malaysia is a flagship of China’s international engagement strategy in higher education. How XMUM adjusts and adapts to the local environment will be an exemplar for other Chinese universities.